Pelatihan Kewirausahaan Bagi Siwa SMK Muhammadiyah 1 Lamongan - Arian Yusuf Wijaksono; Sawabi; Muhammad David; Agung Stiabudi Abdulloh Musyafak (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Entrepreneurship is a field that is still not in demand by teenagers.although the efforts that have been carried out by the government and the private sector have been many, but still need the support of many parties, the purpose of this community service activity is to instill an entrepreneurial spirit from an early age in students. It is expected that in the future students will become reliable and professional entrepreneurs. The number of students fostered in entrepreneurship is 29 people, the method of implementing this activity uses an entrepreneurial training approach accompanied by examples of making frozen food products. The implementation of training activities is carried out by providing material to build an entrepreneurial spirit